1995
DOI: 10.1126/science.267.5204.1635
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Tubule Self-Assembly: Length Dependence on Cooling Rate Through a First-Order Phase Transition

Abstract: The formation kinetics and self-assembly of multilamellar tubules of the diacetylenic phospholipid 1,2-bis(tricosa-10,12-diynoyl)-sn-glycerol-3-phosphocholine formed under controlled cooling rates were studied by x-ray diffraction and optical, atomic force, and scanning electron microscopy. Tubule formation was driven by a reversible first-order phase transition from an intralamellar, chain-melted L(alpha) phase to a chain-frozen L(beta), phase. These observations are the basis of a highly efficient method of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
189
1
2

Year Published

1997
1997
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(202 citation statements)
references
References 23 publications
10
189
1
2
Order By: Relevance
“…The defect regions are stabilized by the segregation of SDS molecules to compensate the highmembrane curvature. As for a surfactant, its preferred packing [16][17][18][19][20] . The HGM molecule has similar area of head group and tail with CPP B1.…”
Section: Discussionmentioning
confidence: 99%
“…The defect regions are stabilized by the segregation of SDS molecules to compensate the highmembrane curvature. As for a surfactant, its preferred packing [16][17][18][19][20] . The HGM molecule has similar area of head group and tail with CPP B1.…”
Section: Discussionmentioning
confidence: 99%
“…Microtubules have a lumen diameter of approximately 0.5 mm and an average length of 20 45 mm, that provides large storage volume relative to the diameter. 71,74) They are stable in physiological solutions at 37oC for prolonged periods of time. 75,76) Lipid microtubules are safe, non-in‰ammatory and provide ease of site speciˆc delivery for proteins and peptides.…”
Section: Oil Suspensionsmentioning
confidence: 99%
“…It has been found that a variety of amphiphilies, including alkylaldonamides (3), diacetylenic phospholipids (4,5), amino acid-based surfactants (6,7), and multicomponent mixtures in bile (8,9), selfassemble into cylindrical tubules in solutions. Recently, advances have been made in controlling the sizes and shapes of tubules by adjusting the chemical compositions and the conditions under which self-assembly occurs (10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%